2023
DOI: 10.1590/1519-6984.269317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial effect of the Origanum vulgare L essential oil on strains of Klebsiella pneumoniae

Abstract: Bacteria may be the initial cause of certain pathologies as well as a secondary agent responsible for the development of complications such as pressure ulcer infections. Pressure ulcers are a persistent health problem, especially in immunocompromised patients, and associated with infection by opportunistic microorganisms with antimicrobial resistance, such as Klebsiella pneumoniae, highlight the need for the development of new antimicrobial approaches. Thus, the aim of this study was to evaluate the antibacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The observed strong inhibitory activity and bactericidal/bacteriostatic effect of oregano essential oil against strains of K. pneumoniae, P. aeruginosa, and S. saprophyticus from meat products may be attributed to the composition of this substance. Silva et al (2023) identified a total of nine constituents in O. vulgare oil from the Quinari brand, namely, alpha-pinene, camphene, myrcene, carene, cymene, gamma-terpinene, linalool, carvacrol, and caryophyllene, with carvacrol being the major compound at a high percentage (40.52%). Carvacrol is known to damage the lipid plasma membranes of bacteria, hindering cell division and causing cell dehydration (Araújo & Longo, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The observed strong inhibitory activity and bactericidal/bacteriostatic effect of oregano essential oil against strains of K. pneumoniae, P. aeruginosa, and S. saprophyticus from meat products may be attributed to the composition of this substance. Silva et al (2023) identified a total of nine constituents in O. vulgare oil from the Quinari brand, namely, alpha-pinene, camphene, myrcene, carene, cymene, gamma-terpinene, linalool, carvacrol, and caryophyllene, with carvacrol being the major compound at a high percentage (40.52%). Carvacrol is known to damage the lipid plasma membranes of bacteria, hindering cell division and causing cell dehydration (Araújo & Longo, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The high incidence of resistant Candida species and the associated negative consequences and therapeutic limitations make it crucial to develop effective, inexpensive, and nontoxic alternative treatments. In this sense, OEO has demonstrated good fungicidal and bactericidal activities against different pathogens ( 28 30 ). Recent studies also showed that the volatile part of the EO (VP-OEO) has interesting antimicrobial activity ( 31 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study has revealed synergistic interactions between oregano essential oils and selected antibiotics. The works of Wendy et al, 2012 [14,[65][66][67], on the use of Origanum essential oils in combination with antibiotics have shown significant synergistic interactions. Our results support these studies by showing that Origanum essential oils have a synergistic effect on antibiotic-resistant bacteria, such as Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Acinetobacter baumannii, which are frequently responsible for infections linked to healthcare settings.…”
Section: Discussionmentioning
confidence: 99%